The Effect of Wordwall on Bilingual Mathematics Learning Motivation in Elementary School - Muhimmatul Ulya; Aris Kuswanto (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examined changes in elementary students' motivation after the implementation of Wordwall in bilingual mathematics learning. This study used a quantitative pre-experimental one-group pretest-posttest design. The participants were 28 fourth-grade students at MI Bilingual Roudlotul Jannah Sidoarjo, Indonesia. Data were collected using a learning motivation questionnaire based on Keller's ARCS model, which includes Attention, Relevance, Confidence, and Satisfaction. The instrument was validated using Pearson's Product-Moment correlation and tested for reliability using Cronbach's Alpha. The data were analyzed using descriptive statistics, N-Gain analysis, the Shapiro-Wilk normality test, a paired sample t-test, and Cohen's effect size. The findings showed that students' mean motivation score increased from 63.18 in the pretest to 87.79 in the posttest. The N-Gain score was 0.6794, indicating moderate improvement. The paired-samples t-test showed a significant difference between the pretest and posttest scores, and Cohen's dz indicated a very large effect size. These findings suggest that Wordwall can serve as a promising interactive digital learning medium for supporting students' motivation in bilingual mathematics learning. However, because this study used a pre-experimental design without a control group, the results should be interpreted as evidence of motivational improvement within the observed classroom rather than as definitive causal proof of Wordwall's effectiveness.